Mucous membrane pemphigoid involving palmoplantar lesions that developed during adjuvant nivolumab for malignant melanoma: A rare case and literature review - Takata, Mayumi; Usui, Shunya; Kogame, Toshiaki; Otsuka, Atsushi; Kabashima, Kenji (Trends in Immunotherapy, 2023)
Immune checkpoint inhibitors (ICIs), such as nivolumab, which target anti‐programmed cell death-1 (PD-1), have been applied to a variety of cancers and have caused immune‐related adverse events (irAEs). Although an association between ICIs and bullous pemphigoid and mucosal pemphigoid (MMP) has been reported, the complex mechanisms underlying PD-1 inhibition‐induced autoantibody production and autoimmunity remain unelucidated. In this report, we present a unique case of MMP involving the palmoplantar lesions during adjuvant nivolumab therapy. A Japanese woman in her 70s was treated with nivolumab for postoperative vulvar malignant melanoma; after the 12th cycle of treatment, ulcers were seen in the oral cavity, and 4 months later, tense palmoplantar blisters appeared. Microscopic examination of the palmar blister revealed subepidermal vesicles characterized by eosinophil infiltration. Immunofluorescence analysis revealed linear IgG and C3 deposits along the basement membrane; ELISA testing confirmed the presence of anti‐BP180 NC16A IgG antibody, and MMP was diagnosed. The patient’s condition gradually improved with a therapeutic regimen of corticosteroids and immunoglobulins. A review of 10 cases of ICI‐associated MMP, including the present case, revealed clinical similarities to conventional MMP; in cases of persistent oral erosions due to ICI, it is most important to consider mucositis and MMP in the framework of differential diagnosis. Besides, we suggest that we can be more suspicious of MMP by paying attention to examining the palms and soles when the patient receiving ICIs has refractory oral ulcers. This report underscores the importance of careful observation and prompt management of irAE as cancer immunotherapy evolves.